2015
DOI: 10.2147/lra.s64806
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic regional blocks: management, challenges, and solutions

Abstract: In the past decade ophthalmic anesthesia has witnessed a major transformation. The sun has set on the landscape of ophthalmic procedures performed under general anesthesia at in-hospital settings. In its place a new dawn has ushered in the panorama of eye surgeries conducted under regional and topical anesthesia at specialty eye care centers. The impact of the burgeoning geriatric population is that an increasing number of elderly patients will present for eye surgery. In order to accommodate increased patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 84 publications
0
47
0
2
Order By: Relevance
“…Ultrasonografi kullanımı ile göz küresi, optik sinir, anatomik yapılar, iğnenin ilerletildiği yol ve ilacın yayılımı eş zamanlı olarak gösterilerek daha güvenli ve kaliteli blok sağlanabilmektedir (11,12). Bunun yanında ultrasonografi uygulaması daha uzun zaman almaktadır.…”
Section: Discussionunclassified
“…Ultrasonografi kullanımı ile göz küresi, optik sinir, anatomik yapılar, iğnenin ilerletildiği yol ve ilacın yayılımı eş zamanlı olarak gösterilerek daha güvenli ve kaliteli blok sağlanabilmektedir (11,12). Bunun yanında ultrasonografi uygulaması daha uzun zaman almaktadır.…”
Section: Discussionunclassified
“…Sight threatening complications include retro-and peribulbar hemorrhage, ocular penetration and perforation, retinal vascular spasm, optic nerve injury, and ocular myotoxicity [3] . In an audit of 12,000 retrobulbar blocks, Edge and Nicoll [4] found that patients with acquired vascular disease were at a significantly greater risk of periocular bleeding, whereas diabetics presented only a marginal risk of serious hemorrhage.…”
Section: Retrobulbar Anaesthesiamentioning
confidence: 99%
“…Topical anaesthesia was the common practice pattern for cataract surgery among United States Veteran Health Administration [44] and Canadian ophthalmologists [45] . Palte opinioned that with the changing paradiagm of regional blocks, in future Anaesthesiologists will have to perform blocks and in the holding area and Residents would have to become skilled in performing blocks due to larger patient volumes [3] .…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many believe that the peribulbar block is a safer technique however, it has the disadvantage of a slow onset of orbital akinesia and to produce it a larger volume or repeated injections of anesthetic solution is required due to limited diffusion of local anesthetics (LA) [5]. This also increases the frequency of complications such as globe perforation and hemorrhage [4].…”
Section: Introductionmentioning
confidence: 99%